Peripapillary retinal nerve fiber layer thickness in different glaucoma stages measured by optical coherence tomography - Živković Maja; Jakšić Vesna; Jovanović Predrag; Zlatanović Marko; Zlatanović Gordana; Đorđević-Jocić Jasmina (Vojnosanitetski Pregled)
Background/Aim. One of the most reliable methods for structural measurements of glaucomatous damage is spectral domain optical coherence tomography (SD-OCT). The aim of this study was to measure peripapillary retinal nerve fiber layer (RNFL) thickness with SD-OCT in eyes with different stages of glaucoma, as well as to determine which sector in the peripapillary circle is the most vulnerable to glaucomatous damage. Methods. The study included 153 eyes of 93 patients with confirmed primary open angle glaucoma (POAG). All the patients underwent a complete ophthalmic examination, including visual field testing and peripapillary RNFL thickness measured by SD-OCT. They were divided into three subgroups: early, moderate and severe stage of glaucoma based on the mean deviation (MD) index of visual field. The results were presented as mean RNFL thickness: total, in the four quadrants and 12 clock-hour RNFL thickness. Results. The overall mean peripapillary RNFL was 74.95 ± 14.51 μm. The lower quadrant had the thickest RNFL (92.78 ± 25.84 μm), followed by upper (88.82 ± 22.04 μm), nasal (64.31 ± 11.67 μm) and temporal ones (54.02 ± 12.76 μm), showing a significant difference (χ2 = 273.36, DF = 3, p < 0.001). Comparison between RNFL thickness in early glaucoma and moderate and severe stages revealed that the most sensitive sectors were inferior and superior ones, as well as sectors at 5–7 clock hour position. The greatest decrease in RNFL thickness was observed in the 9 o'clock hour sector in all three glaucoma subgroups (46.99 ± 13.28 μm), while the RNFL was the thickest in the 6 o'clock hour sector (102.63 ± 34.12 μm). Conclusion. Peripapillary RNFL thickness is inversely proportional to the degree of glaucomatous damage: the greater the damage, the thinner peripapillary RNFL.